Central administration of kisspeptin-10 inhibits natriuresis and diuresis induced by blood volume expansion in anesthetized male rats - Han Xu; Yan Ming; An Xiao-fei; He Ming; Yu Jiang-yi (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the possible role of hypothalamic kisspeptin in the regulation of body fluid metabolism and maintenance of internal homeostasis. Methods: Natriuresis and diuresis were induced by blood volume expansion (VE) in anesthetized male rats and kisspeptin-10 was intracerebroventricularly (icv) administered. Radioimmunoassay (RIA) was used to measure the plasma arginine vasopressin (AVP) and atrial natriuretic peptide (ANP) concentrations during the VE. The mediation of the renal sympathetic nerve was also investigated in rats with bilateral renal sympathetic denervation. Results: The increased urine flow and sodium excretion induced by VE were significantly inhibited by icv injection of 5 nmol kisspeptin-10 (P